Using Oxford Smart Choice Multi-ROM to develop the students’ listening ability - Juvrianto Chrissunday Jakob; Nihla Afdaliah (Universitas Islam Sultan Agung, 2019)
The objective of the research aims to investigate whether or not the use of CALL (Computer Assisted Language Learning) with Oxford Smart Choice Multi-ROM as an audiovisual learning software can develop the listening ability of the tenth grade students of SMA Negeri 1 Model Parepare. The research applied quasi-experimental design. The population of this research was the tenth year students of SMA Negeri 1 Model Parepare. The total number of population is 411 students and two classes of twelve classes were taken as sample by using cluster random sampling. The findings of this study as the effect of Oxford Smart Choice Multi-ROM to develop the student’s listening ability, as shown by t-test value (4.6) that higher than t-table value (2.000). It means that the listening ability of the tenth grade students of SMA Negeri 1 Model Parepare develop significantly after they are taught by using CALL (Computer Assisted Language Learning) with Oxford Smart Choice Multi-ROM.